CIPB 2011 SELECTED AWARD - Mouzouropoulos, Theseas (My University, 2026)
The award was received by the The 5th China International Poster Biennial for the exemplary design and concept in the category Poster Design. The poster with the title "World’s Poverty Demographics" addresses the issue of poverty & social exclusion through an alternative composition of data visualisation and info-graphics that emerged through an extensive personal research. These aesthetically unique demographics, describe the global tragic results of poverty & social exclusion the last seven years
Keywords: Arts and entertainment